Energy-saving as an integral part of technical and economic efficiency - Shlychkov, Dmitriy (Opción, 2019)
The technical and economic aspects of the pipeline rehabilitation of water supply systems by various methods are presented and the mechanism for choosing the optimal technology for the minimum energy costs is determined. Based on the results of the calculated data, it was found that the influence of resistivity has a decisive role in energy saving during water transportation through pipelines of a water supply system. In conclusion, as a criterion for evaluating energy saving when implementing trenchless methods for pipeline rehabilitation that retain structural integrity and residual strength.